Current status of hematopoietic cell transplantation in the treatment of systemic amyloid light-chain amyloidosis - Schönland, Stefan; Dreger, Peter; Hegenbart, Ute (Bone marrow transplantation, 2012)
Systemic amyloid light-chain (AL) amyloidosis is a protein conformation disorder caused by clonal plasma cell dyscrasias. Symptoms result from fibrillar extracellular deposits in various tissues. The deposits disrupt organ function and ultimately lead to death. The prognosis is poor and depends mostly on the severity of cardiac involvement. The treatment is derived from the therapy of multiple myeloma with the main goal being to reach a complete hematological remission (CR). High-dose melphalan (HDM) and autologous hematopoietic cell transplantation can induce CR rates in about 40%. The main concern was the high transplant-related mortality of up to 40% due to organ dysfunction, which could be reduced to <12% by careful patient selection in experienced centers. However, >50% of patients in CR survive longer than 10 years, suggesting that HDM has the potential to change the natural course of the disease. As there is evidence that ‘graft-versus-plasma-cell-dyscrasia’ effects are active in AL amyloidosis, allogeneic hematopoietic cell transplantation might be an option for younger patients with preserved organ functions who have relapsed after HDM.